AGU Advances Goes Online. Issue 1 (19th November 2019) - Trumbore, Susan; Barros, Ana; Davidson, Eric; Ehlmann, Bethany; Famiglietti, James; Gruber, Nicolas; Hudson, Mary; Illangasekare, Tissa; Kang, Sarah; Parsons, Tom; Rizzoli, Paola; Salters, Vincent; et al.
Abstract: AGU Advances is a premier open access journal with transparent review and with commentary accompanying the research articles that places their results in a wider context. Key Point: The inaugural editorial board of AGU Advances outlines their vision for the journal